Associative learning potentiates protein kinase C activation in synaptosomes of the rabbit hippocampus. - Sunayashiki-Kusuzaki, K (1993)
Using electrophysiological, biochemical, and autoradiographic techniques, changes in protein kinase C (PKC) activity in specific regions of the hippocampus have been previously implicated in classical conditioning of the nictitating membrane response of the rabbit. Here we report that activation of PKC is potentiated 2- to 3-fold in synaptosomes of the hippocampal CA1 and CA2 to -3 regions in rabbits that have undergone classical conditioning of the nictitating membrane response. This potentiation is apparently due to a change in the biochemical properties of PKC within the synaptosomes and is not a result of an increase in total PKC activity. This observation correlates a subcellular biochemical change with classical conditioning of a mammal.